The construction of Indonesian nature and culture in tourism videos produced by Wonderful Indonesia - Ardiya Ardiya; C Sobarna; Rosaria Mita Amalia; Nani Darmayanti (Studies in English Language and Education, 2025)
Wonderful Indonesia is the trademark of the Indonesian Ministry of Tourism and Creative Economy (Kementerian Pariwisata dan Ekonomi Kreatif or Kemenparekraf), responsible for producing videos aimed at promoting tourism to national and international tourists. Consequently, this study seeks to examine the representation of identity in the construction of Indonesian nature and culture. Based on this perspective, the selected video for analysis was Wonderful Indonesia Challenge: Borobudur, and the use of the multimodal discourse analysis showed that Indonesian nature and culture were constructed uniquely in this video. Additionally, the selected video represented nature in diverse tourist destinations as exotic, beautiful, friendly, comfortable, and pleasant. Traditional culture was also portrayed as preserved by the local community, even in daily activities. The glorification of locality was increasingly felt when tourists were proven to be actively engaged and happy. Simultaneously, local people in the video were shown to be passive but friendly. However, this video did not portray traditional culture as being close to tourists. The entire scenario was relatively open, enjoyable, and experienced, and even recorded by tourists, despite the sacred nature of the ritual performed. This condition gave the impression that Indonesian nature and culture were exotic, beautiful, unrestricted, comfortable, safe, and enjoyable.